2020
DOI: 10.1093/ajcp/aqaa093
|View full text |Cite|
|
Sign up to set email alerts
|

Age- and Sex-Specific Pediatric Reference Intervals of Serum Electrolytes in Jilin Province of China Using the A Priori Approach

Abstract: Objectives The purpose of this study was to establish age- and sex-specific pediatric reference intervals of serum potassium (K), sodium (Na), chlorine (Cl), calcium (Ca), magnesium (Mg), and phosphorus (P) using a direct sampling technique. Methods In accordance with the a priori approach, healthy individuals (n = 6,466, aged 1 month to <18 years) were enrolled from five regions in Jilin Province, China, and all analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
11
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 34 publications
3
11
1
Order By: Relevance
“…The manufacturer RIs were less reliable in the evaluation of clinical applicability before use in Chinese laboratories, because they were generally based on Caucasian people and lacked data on children. The RIs of Cl, K and Na were similar to those from reagent inserts and previous ndings for children and adolescents [4]. Therefore, it seemed that the three electrolytes remained relatively stable in one's life.…”
Section: Comparison To Other Studiessupporting
confidence: 81%
See 2 more Smart Citations
“…The manufacturer RIs were less reliable in the evaluation of clinical applicability before use in Chinese laboratories, because they were generally based on Caucasian people and lacked data on children. The RIs of Cl, K and Na were similar to those from reagent inserts and previous ndings for children and adolescents [4]. Therefore, it seemed that the three electrolytes remained relatively stable in one's life.…”
Section: Comparison To Other Studiessupporting
confidence: 81%
“…Previous research has found that the differences in RIs of analytes are due to their complex patterns of biological sources of variations, such as region, race, diet, and more individual characteristic [1,2]. Data from the studies we have published con rms that establishing age-and sexappropriate local RIs is more accurate and reliable for providing clinical decision support, especially in pediatrics [3][4][5][6].…”
Section: Introductionmentioning
confidence: 68%
See 1 more Smart Citation
“…In particular, all responses to these were voluntary. The exclusion criteria, described in detail in previous publications, 8 were as follows:…”
Section: Methodsmentioning
confidence: 99%
“…In particular, all responses to these were voluntary. The exclusion criteria, described in detail in previous publications, 8 were as follows: ① Presence of acute or chronic diseases which require medical intervention; ② Weight and height more than 10% of the average at the same-sex; ③ Use of medications in the past 2 weeks; ④ Surgery ⑫ White blood cell count <3.0 × 10 9 /l or >12.0 × 10 9 /l; ⑬ Hemoglobin <120 g/l (male) or <110 g/l (female).…”
Section: Exclusion Criteriamentioning
confidence: 99%